The Compound 2-Hexyl, 5-Propyl Resorcinol Has a Key Role in Biofilm Formation by the Biocontrol Rhizobacterium Pseudomonas chlororaphis PCL1606 - Calderón, Claudia E.; Tienda, Sandra; Heredia-Ponce, Zaira; Arrebola, Eva; Cárcamo-Oyarce, Gerardo; Eberl, Leo; Cazorla, Francisco M. (Frontiers in Microbiology, 2019)
The production of the compound 2-hexyl-5-propyl resorcinol (HPR) by the biocontrol rhizobacterium Pseudomonas chlororaphis PCL1606 (PcPCL1606) is crucial for fungal antagonism and biocontrol activity that protects plants against the phytopathogenic fungus Rosellinia necatrix. The production of HPR is also involved in avocado root colonization during the biocontrol process. This pleiotrophic response prompted us to study the potential role of HPR production in biofilm formation. The swimming motility of PcPLL1606 is enhanced by the disruption of HPR production. Mutants impaired in HPR production, revealed that adhesion, colony morphology and typical air-liquid interphase pellicles were all dependent on HPR production. The role of HPR production in biofilm architecture was also analysed in flow chamber experiments. These experiments revealed that the HPR mutant cells had less tight unions than those producing HPR, suggesting an involvement of HPR in the production of the biofilm matrix.